Educational Commons: Democratic Values, Social Justice and Inclusion in Education - Cappello, Gianna; Siino, Marianna; Fernandes, Natália; Arciniega-Caceres, Mittzy (UNIPA Springer Series, 2024)
This open access book presents the final findings from the case studies developed within the Horizon 2020 SMOOTH project Educational Spaces. Passing through Enclosures and Reversing Inequalities through Educational Commons. The overall objective of the project was to understand, develop, and accelerate the potential impact of education on reversing inequalities for active social inclusion of children and young people at risk in Europe, through introducing the emergent paradigm of the “commons” as an alternative value and action system in the field of education (preschools, schools, and after-school programs). SMOOTH critically draws out the implications of the commons for refiguring education and for social change in general, on a footing of equality, sharing, participation, togetherness, caring, and freedom. Universities, research laboratories, municipalities, NGOs, museums, and youth organizations, in different European countries, have worked together to achieve the aboveaim involving almost 200 educators and teachers, and 800 children, and providing interesting insights and suggestions on how to implement educational commons in many different educational contexts. The target audience comprises policymakers and education leaders, students from Education and Communication degrees, researchers, and educators from both formal and non-formal educational contexts.